Exhaled Nitric Oxide Is Useful in Symptomatic Radioactive Pneumonia: A Retrospective Study - Li, Jiancheng; Fu, Xiaobin; Fu, Jie (Mediators of Inflammation, 2017)
The aim was to defect the exhaled nitric oxide (eNO) prediction value of symptomatic radioactive pneumonia (SRP). 64 cases of lung cancer or esophagus cancer, who had the primary radiotherapy (intensity-modulated radiation therapy), were included from 2015 June to 2016 January. During the following, the patients were divided: the symptomatic radiation pneumonia group (SRP, with the CTCAE v4.0 score > 2) and the asymptomatic radiation pneumonia group (ASRP, with CTCAE v4.0 score ≤ 1). All the patients were measured eNO before and at the end of thoracic radiotherapy and gain the posttherapy eNO value and the eNO ratio (posttherapy eNO value/pretherapy eNO value), then the predictive values of eNO toward SRP were measured using the receiver-operating characteristic (ROC). 17 cases were included in the SRP group and the other 47 were included in the ASRP group. The posttherapy eNO was 29.35 (19~60) bbp versus 20.646 (11~37) (P<0.001), and the ratio was 1.669 (0.61~3.5) versus 0.920 (0.35~1.5) (P<0.01) (symptomatic versus asymptomatic). ROC showed that the cutoff value of SRP was 19.5 bbp (posttherapy eNO, area under concentration-time curve (AUC) = 0.879) and 1.305 (eNO ratio, AUC = 0.774), which meant that posttherapy eNO and eNO ratio were useful in finding SRP.